Metal-clad laminates and flexible circuit boards
A metal-clad laminate with a specific polyimide resin composition and controlled loop stiffness addresses the issue of insulating layer tearing and metal layer disconnection in FPCs, enabling repeated 180° bending and improved durability.
Patent Information
- Application Number
- JP2020216877
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2020-12-25
- Publication Date
- 2025-01-23
- Estimated Expiration
- 2040-12-25
AI Technical Summary
Flexible circuit boards (FPCs) used in small electronic devices like smartphones require high bending resistance but face issues with insulating layer tearing and metal layer disconnection due to bending fatigue when the insulating layer is made too thin.
A metal-clad laminate is developed with a specific polyimide resin composition and controlled loop stiffness, featuring a polyimide insulating layer with a thickness of 6 to 18 μm, composed of tetracarboxylic acid residues and diamine residues, and a laminated structure of low and high thermal expansion polyimide layers, ensuring a loop stiffness value of 1 N/m to 6 N/m.
The laminate provides improved bending resistance, allowing repeated 180° bending without tearing or disconnection, suitable for electronic components with frequent bending, such as foldable device hinges, with enhanced durability and stress distribution.
Smart Images

Figure 0007620428000005 
Figure 0007620428000006 
Figure 0007620428000007
Abstract
Description
[Technical field]
[0001] The present invention relates to a metal-clad laminate and a flexible circuit board having excellent bending resistance. [Background technology]
[0002] In recent years, flexible printed circuits (FPCs) have been widely used in electronic devices such as mobile phones, smartphones, notebook personal computers, hard disk drives, optical pickup devices, printers, etc. Because FPCs allow for three-dimensional, high-density mounting even in a limited space, their applications are expanding to include wiring for moving parts of electronic devices such as HDDs, DVDs, mobile phones, and smartphones, as well as cables, connectors, and other components.
[0003] In particular, FPCs used in small electronic devices such as smartphones require high flexibility to withstand repeated 180° bending tests.
[0004] In response to this demand, it has been proposed to set the loop stiffness of a copper-clad laminate to 0.30 N / cm or less by setting the thickness of the insulating layer to 16 μm or less and the thickness of the metal layer to 20 μm or less in a flexible copper-clad laminate used in a flexible circuit board, and a copper-clad laminate with a loop stiffness of 0.20 to 0.49 N / cm is shown in the examples. Here, the loop stiffness is a value measured using a loop stiffness tester manufactured by Toyo Seiki under the conditions of a sample width of 5 to 10 mm, a loop length of 50 mm, and a crushing distance of 10 mm.
[0005] It has also been proposed to improve bending resistance by setting the thickness of the polyimide layer at 10 to 25 μm, the thickness of the copper foil at 8 to 20 μm, and setting the average crystal grain size in the cross section in the thickness direction of the copper foil to 10 μm or more (Patent Document 2). [Prior art documents] [Patent documents]
[0006] [Patent Document 1] JP 2007-313854 A [Patent Document 2] JP 2014-80021 A Summary of the Invention [Problem to be solved by the invention]
[0007] The insulating layer of the metal-clad laminate functions as a support for the metal layer. Therefore, by making the insulating layer thinner, the bending resistance of the metal-clad laminate can be improved to some extent. However, if the insulating layer is made too thin, the insulating layer becomes more susceptible to cracking, and the metal layer becomes more susceptible to breakage due to bending fatigue.
[0008] Therefore, an object of the present invention is to provide an FPC with improved flex resistance without causing cracks in the insulating layer or breaks in the metal layer due to flex fatigue, and to provide a metal-clad laminate for use in producing such an FPC. [Means for solving the problem]
[0009] The present inventors conceived that the above-mentioned problems could be solved by forming the insulating resin using a specific polyimide resin and adjusting the loop stiffness value of the metal-clad laminate to fall within a specific range, and thus completed the present invention.
[0010] That is, the present invention provides a metal-clad laminate having a metal layer laminated on one surface of a polyimide insulating layer including a single or multiple polyimide layers, a metal-clad laminate for a flexible circuit board for an electronic component, in which an operation of bending the second non-bent portion 180 degrees relative to the first non-bent portion is repeated so as to obtain a shape including a first non-bent portion and a second non-bent portion whose shape has not changed compared to a flat state, and a bent portion that is located between the first non-bent portion and the second non-bent portion and that has been curved and deformed; The loop stiffness value of the test piece of the metal-clad laminate (width 12.7 mm, loop length 60 mm, crush distance 15 mm) is 1 N / m or more and 6 N / m or less, The present invention provides a metal-clad laminate, characterized in that the polyimide constituting the main layer of the polyimide insulating layer contains tetracarboxylic acid residues and diamine residues, and the diamine residues derived from the diamine compound represented by the following general formula (1) are 20 or more parts by mole per 100 parts by mole of the total diamine residues:
[0011] [ka] [In formula (1), the linking group Z represents a single bond or -COO-, Y represents a monovalent hydrocarbon having 1 to 3 carbon atoms, which may be substituted with a halogen or a phenyl group, an alkoxy group having 1 to 3 carbon atoms, a perfluoroalkyl group having 1 to 3 carbon atoms, or an alkenyl group, n represents 1 or 2, and p and q represent independently an integer of 0 to 4.]
[0012] The present invention also provides a flexible circuit board having a metal layer of the above-mentioned metal-clad laminate that is wired. Effect of the Invention
[0013] The polyimide insulating layer used in the metal-clad laminate of the present invention has improved flex resistance and is excellent in resistance to repeated bending. Therefore, when the metal-clad laminate of the present invention is used, it is possible to repeatedly bend the insulating layer by 180° without causing breakage due to flexural fatigue of the metal layer. Therefore, it is possible to obtain a flexible circuit board suitable for use in electronic components in which bending is repeated, such as in hinge parts of foldable devices, and the bending angle may reach 180°. [Brief description of the drawings]
[0014] [Figure 1] FIG. 1 is an explanatory diagram of a method for measuring the loop stiffness value. [Diagram 2]FIG. 2 is a plan view of a meandering wiring formed on a metal-clad laminate. [Diagram 3] FIG. 3 is an explanatory diagram of the bending operation of the metal-clad laminate on which the meandering wiring is formed. [Figure 4A] FIG. 4A is a side view of a test piece placed on the stage of a bending resistance test apparatus. [Figure 4B] FIG. 4B is a side view of the test piece placed on the stage of the bending resistance test apparatus. [Figure 5A] FIG. 5A is a side view of a test piece bent by rotation of a stage of a bending resistance test device. [Figure 5B] FIG. 5B is a side view of the test piece bent by rotation of the stage of the bending resistance test device. [Figure 6] FIG. 6 shows the measured values of loop stiffness and average number of flexions for Examples 1 to 3. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0015] The present invention will now be described in detail with reference to the drawings, in which the same reference numerals represent the same or equivalent components. <Overall composition> The metal-clad laminate of the present invention is a metal-clad laminate for flexible circuit boards, in which a metal layer is laminated on one side of a polyimide insulating layer including a single or multiple polyimide layers. This metal-clad laminate is usually formed into a long film shape. An FPC is produced by subjecting the metal layer of the metal-clad laminate to wiring processing.
[0016] <Polyimide insulating layer> The polyimide insulating layer constituting the metal-clad laminate is formed from a single layer or multiple layers of polyimide insulating layers. The thickness of the polyimide insulating layer (total thickness in the case of multiple layers) is preferably 6 to 18 μm, more preferably 6 to 10 μm. Since the polyimide insulating layer in the present invention has a specific polyimide composition as described later, if the thickness of the polyimide insulating layer is less than 6 μm, the rigidity of the polyimide insulating layer is too low, so that the bending resistance of the FPC decreases, and handling during processing of the FPC becomes difficult. On the other hand, if the thickness of the polyimide insulating layer exceeds 18 μm, the rigidity of the FPC becomes too high, so that the bending resistance is likely to decrease.
[0017] The polyimide insulating layer is preferably a multi-layer structure, and specifically, the polyimide insulating layer is preferably a laminate structure including a low thermal expansion polyimide layer and a high thermal expansion polyimide layer. Here, the low thermal expansion polyimide layer has a thermal expansion coefficient of 35×10 -6 / K, preferably less than 1×10 -6 ~30×10 -6 / K, particularly preferably 3×10 -6 ~25×10 -6 / K. A high thermal expansion polyimide layer is a polyimide layer with a thermal expansion coefficient of 35×10 -6 / K or more, preferably 35×10 -6 ~80×10 -6 / K, particularly preferably 35×10 -6 ~70×10 -6 / K. The polyimide layer can be made to have a desired thermal expansion coefficient by appropriately changing the combination of raw materials used, the thickness, and the drying and curing conditions.
[0018] <Polyimide layer composition> The polyimide composition of the polyimide insulating layer is such that the polyimide constituting the main layer of the polyimide insulating layer contains tetracarboxylic acid residues and diamine residues, and the diamine residues derived from the diamine compound represented by the following general formula (1) are 20 molar parts or more per 100 molar parts of all diamine residues. Here, the main layer refers to a layer that occupies 50% or more of the thickness of the entire polyimide layers when the polyimide insulating layer is formed from multiple polyimide layers.
[0019] [ka] [In formula (1), the linking group Z represents a single bond or -COO-, Y represents a monovalent hydrocarbon having 1 to 3 carbon atoms, which may be substituted with a halogen or a phenyl group, an alkoxy group having 1 to 3 carbon atoms, a perfluoroalkyl group having 1 to 3 carbon atoms, or an alkenyl group, n represents 1 or 2, and p and q represent independently an integer of 0 to 4.]
[0020] Examples of the compound represented by formula (1) include paraphenylenediamine (PDA), 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB), 2,2'-n-propyl-4,4'-diaminobiphenyl (m-NPB), 2'-methoxy-4,4'-diaminobenzanilide (MABA), 4,4'-diaminobenzanilide (DABA), and 2,2'-bis(trifluoromethyl)benzidine (TFMB).
[0021] By using the diamine compound represented by general formula (1) in the amount within the above range, an ordered structure is formed throughout the polymer due to the rigid structure derived from the monomer, so that the thermal expansion and toughness of the polyimide film can be reduced. In addition, since it contains two or more benzene rings, it is advantageous to reduce the imide group concentration and contribute to low moisture absorption. From this point of view, it is preferable that the diamine residue derived from the diamine compound represented by general formula (1) is contained in an amount of 20 molar parts or more, preferably 50 molar parts or more, and more preferably 60 molar parts or more, per 100 molar parts of the total diamine residues.
[0022] In particular, in the compound represented by formula (1), m-TB: 2,2'-dimethyl-4,4'-diaminobiphenyl and TFMB: 2,2'-bis(trifluoromethyl)benzidine is preferably 20 mol % or more of the diamine compounds constituting the polyimide insulation layer. When the polyimide insulation layer is composed of multiple layers, the above m-TB and TFMB are preferably contained in 50 mol % or more of the diamine compounds constituting the entire polyimide insulation layer.
[0023] On the other hand, as the acid forming the tetracarboxylic acid residue of the polyimide insulating layer, biphenyltetracarboxylic dianhydride, pyromellitic dianhydride, etc. can be used. Specific examples of biphenyltetracarboxylic dianhydride include 3,3',4,4'-biphenyltetracarboxylic dianhydride, 2,3',3,4'-biphenyltetracarboxylic dianhydride, 2,2',3,3'-biphenyltetracarboxylic dianhydride, etc. In particular, it is preferable that the tetracarboxylic acid residue in the polyimide insulating layer contains at least one of the tetracarboxylic acid residue derived from pyromellitic dianhydride or the tetracarboxylic acid residue derived from 3,3',4,4'-biphenyltetracarboxylic dianhydride, and the total of the tetracarboxylic acid residues is 50 mol% or more with respect to 100 mol parts of the total tetracarboxylic acid residues.
[0024] In forming the polyimide insulating layer, an acid anhydride other than the above may be contained. Examples of the acid anhydride other than the above include 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride, 4,4'-oxydiphthalic anhydride, 2,2',3,3'-, 2,3,3',4'- or 3,3',4,4'-benzophenonetetracarboxylic dianhydride, 2,3',3,4'-diphenylethertetracarboxylic dianhydride, bis(2,3-dicarboxyphenyl)ether dianhydride, 3,3'',4,4''-, 2,3,3'',4''- or 2,2'',3,3''-p-terphenyltetracarboxylic dianhydride, 2,2-bis(2,3- or 3,4-dicarboxyphenyl)-propane dianhydride, bis(2,3- or 3,4-dicarboxyphenyl)-propane dianhydride, and bis(2,3- or 3,4-dicarboxyphenyl)-propane dianhydride.4-dicarboxyphenyl)methane dianhydride, bis(2,3- or 3,4-dicarboxyphenyl)sulfone dianhydride, 1,1-bis(2,3- or 3,4-dicarboxyphenyl)ethane dianhydride, 1,2,7,8-, 1,2,6,7- or 1,2,9,10-phenanthrene-tetracarboxylic dianhydride, 2,3,6,7-anthracene tetracarboxylic dianhydride, 2,2-bis(3,4-dicarboxyphenyl)tetrafluoropropane dianhydride, 2,3,5,6-cyclohexane dianhydride, 2,3,6,7-naphthalene tetracarboxylic dianhydride, 1,2,5,6-naphthalene tetracarboxylic dianhydride, 1,4,5,8-naphthalene tetracarboxylic dianhydride, 4,8-dimethyl-1,2,3,5,6,7-hexahydronaphthalene-1,2,5,6-tetracarboxylic dianhydride, 2 ,6- or 2,7-dichloronaphthalene-1,4,5,8-tetracarboxylic dianhydride, 2,3,6,7-(or 1,4,5,8-)tetrachloronaphthalene-1,4,5,8-(or 2,3,6,7-)tetracarboxylic dianhydride, 2,3,8,9-, 3,4,9,10-, 4,5,10,11- or 5,6,11,12-perylene-tetracarboxylic dianhydride, cyclopentane-1,2,3, 4-tetracarboxylic dianhydride, pyrazine-2,3,5,6-tetracarboxylic dianhydride, pyrrolidine-2,3,4,5-tetracarboxylic dianhydride, thiophene-2,3,4,5-tetracarboxylic dianhydride, 4,4'-bis(2,3-dicarboxyphenoxy)diphenylmethane dianhydride, 2,2-bis[4-(3,4-dicarboxyphenoxy)phenyl]propane dianhydride, etc.
[0025] In addition, the thermal expansion coefficient is 35×10 -6To obtain a polyimide layer with a high thermal expansion of 1000000000 / K or more, for example, pyromellitic dianhydride, 3,3',4,4'-biphenyltetracarboxylic dianhydride, 3,3',4,4'-benzophenonetetracarboxylic dianhydride, and 3,3',4,4'-diphenylsulfonetetracarboxylic dianhydride are used as raw material acid anhydride components, and 2,2'-bis[4-(4-aminophenoxy)phenyl]propane, 4,4'-diaminodiphenyl ether, and 1,3-bis(4-aminophenoxy)benzene are used as diamine components, and particularly preferably pyromellitic dianhydride and 2,2'-bis[4-(4-aminophenoxy)phenyl]propane are used as the main components of the raw material components. The preferred glass transition temperature of the high thermal expansion polyimide layer obtained in this manner is within the range of 300 to 400 ° C.
[0026] Furthermore, when the polyimide insulating layer has a laminated structure of a low thermal expansion polyimide layer and a high thermal expansion polyimide layer, the thickness ratio of the low thermal expansion polyimide layer to the high thermal expansion polyimide layer (low thermal expansion polyimide layer / high thermal expansion polyimide layer) is preferably within the range of 2 to 15. If this ratio is less than 2, the low thermal expansion polyimide layer becomes thin relative to the entire polyimide insulating layer, making it difficult to control the dimensional accuracy and loop stiffness of the polyimide film, and for example, the dimensional change rate when a metal layer is etched to form a circuit wiring layer increases, while if it exceeds 15, the high thermal expansion polyimide layer becomes thin, reducing the adhesive reliability between the polyimide insulating layer and the circuit wiring layer.
[0027] The polyimide insulating layer of the metal-clad laminate of the present invention can be produced by reacting the diamine component and the acid anhydride component in a solvent to generate polyamic acid, followed by heating and ring-closing. For example, the diamine component and the acid anhydride component are dissolved in an organic solvent in approximately equal moles, and the mixture is stirred at a temperature in the range of 0 to 100°C for 30 minutes to 24 hours to polymerize, thereby obtaining polyamic acid, which is a precursor of polyimide. In the reaction, the reaction components are dissolved so that the precursor generated is in the range of 5 to 30% by weight, preferably in the range of 10 to 20% by weight, in the organic solvent. Examples of organic solvents used in the polymerization reaction include N,N-dimethylformamide, N,N-dimethylacetamide (DMAC), N-methyl-2-pyrrolidone, 2-butanone, dimethylsulfoxide, dimethyl sulfate, cyclohexanone, dioxane, tetrahydrofuran, diglyme, triglyme, and the like. Two or more of these solvents can be used in combination, and further, aromatic hydrocarbons such as xylene and toluene can also be used in combination. The amount of organic solvent used is not particularly limited, but it is preferable to adjust the amount of organic solvent used so that the concentration of the polyamic acid solution (polyimide precursor solution) obtained by the polymerization reaction is about 5 to 30% by weight. The synthesized precursor is usually advantageously used as a reaction solvent solution, but can be concentrated, diluted, or replaced with another organic solvent if necessary. The precursor is generally advantageously used because it has excellent solvent solubility.
[0028] In the synthesis of polyimide, the above-mentioned acid anhydrides and diamines may be used alone or in combination of two or more. By selecting the types of diamines and acid anhydrides, or the molar ratios of two or more diamines or acid anhydrides, the thermal expansion, adhesiveness, storage modulus, glass transition temperature, etc. can be controlled. In addition, when the polyimide has a plurality of polyimide structural units, they may be present as blocks or randomly, but are preferably present randomly.
[0029] The weight-average molecular weight of the polyamic acid constituting the polyimide insulating layer is, for example, preferably in the range of 10,000 to 400,000, more preferably in the range of 50,000 to 350,000. If the weight-average molecular weight is less than 10,000, the strength of the polyimide insulating layer tends to decrease and become brittle due to coating. On the other hand, if the weight-average molecular weight exceeds 400,000, the viscosity increases excessively, and defects such as uneven thickness and streaks in the coating layer tend to occur during the coating process.
[0030] More specific examples of the manufacturing method of the metal-clad laminate of the present invention include a method of applying a polyamic acid solution to a supporting substrate, drying the solution, and then imidizing the polyimide insulating layer (casting method), a method of applying a polyamic acid solution to a supporting substrate, drying the solution, peeling off the polyamic acid gel film from the supporting substrate, and then imidizing the polyimide insulating layer, and the like. In addition, examples of manufacturing methods when the polyimide insulating layer of the metal-clad laminate is composed of multiple layers include a method of repeatedly applying a polyamic acid solution to a supporting substrate and drying the solution, and then imidizing the polyimide insulating layer (sequential coating method), and a method of simultaneously applying a polyamic acid laminate structure to a supporting substrate by multilayer extrusion, drying the laminate structure, and then imidizing the polyimide insulating layer (multilayer extrusion method). There are no particular limitations on the method of applying the polyamic acid solution to the substrate, and it is possible to apply the solution using a coater such as a comma, die, knife, or lip. When forming a multilayer polyimide layer, a method of repeatedly applying a polyimide solution or a polyamic acid solution to a substrate and drying the solution is preferable.
[0031] <Metal layer> The material of the metal layer constituting the metal-clad laminate of the present invention is not particularly limited, and examples thereof include copper, stainless steel, iron, nickel, beryllium, aluminum, zinc, indium, silver, gold, tin, zirconium, tantalum, titanium, lead, magnesium, manganese, and alloys thereof. Among these, copper or copper alloys are particularly preferred.
[0032] There is no particular limitation on the method for forming the metal layer, and for example, a seed layer may be formed by sputtering a metal on a polyimide insulating layer, and then the metal layer may be formed by plating, or a metal foil may be laminated on a polyimide insulating layer by a method such as thermocompression bonding, to form a metal layer. Also, a laminate of a polyimide layer and a metal layer may be formed by casting a coating liquid containing a polyamic acid, which is a precursor of the above-mentioned polyimide insulating layer, on a metal foil, drying the coating film, and then heat-treating the coating film to imidize it.
[0033] Furthermore, the metal-clad laminate of the present invention has a metal layer on one side of the polyimide insulating layer, but may have a metal layer on the other side as required to form a double-sided metal-clad laminate.
[0034] <Thickness ratio of polyimide insulating layer to metal layer> In the metal-clad laminate of the present invention, the ratio of the thickness of the polyimide insulating layer (not limited to that formed from the diamine compound of formula (1)) to the thickness of the metal layer is preferably 0.3 to 2.0, more preferably 0.3 to 1.0, and even more preferably 0.4 to 1.0. If this ratio is less than 0.3, the electrical capacity transmitted and received in the FPC circuit will be insufficient, and it will be difficult to achieve excellent flex resistance by setting the loop stiffness value within a specific range. On the other hand, if this ratio exceeds 2.0, the flex resistance will also decrease.
[0035] <Thickness of metal-clad laminate> The total thickness of the polyimide insulating layer (not limited to those formed from the diamine compound of formula (1)) and the metal layer is preferably 15 μm to 36 μm, more preferably 16 μm to 24 μm. If the thickness of the metal-clad laminate is less than 15 μm, the rigidity is too low, making it difficult to handle during the manufacture of the FPC. On the other hand, if the thickness exceeds 36 μm, the rigidity is too high, resulting in portions of the wiring layer receiving large stress when the FPC is bent, and the bending resistance decreases when bending is performed continuously.
[0036] Therefore, for example, when 180° bending tests are performed continuously, the number of bending times until the resistance value of the wiring layer exceeds a predetermined value decreases. That is, as shown in Fig. 2, meandering wiring 201 is formed in the metal layer with linear wiring parts (length A = 110 mm) arranged in parallel with wiring width L / space width S = 100 μm / 100 μm, and the longitudinal direction (X-axis direction) of meandering wiring 201 is inverted 180° as shown by the arrow in Fig. 3 and folded in half to bend the metal-clad laminate on which meandering wiring 201 is formed, and a first non-bending portion 110, a second non-bending portion 120, and a bent portion 130 between the first non-bending portion 110 and the second non-bending portion 120 are formed. In this case, the axial direction parallel to the thickness direction of first non-bending portion 110 and second non-bending portion 120 is defined as the Y-axis direction, and the direction perpendicular to this and longitudinal direction of the wiring of non-bending portions 110, 120 is defined as the X-axis direction, and in the two-dimensional coordinate axes in the X-axis and Y-axis directions, when the maximum length Lx of the bent portion in the X-axis direction is 1.0 mm or more and 10.0 mm or less and the maximum length Ly of the bent portion in the Y-axis direction is 1.0 mm or more and 6.0 mm or less, the number of bends at which the resistance of meandering wiring 201 increases by 10% compared to before the start of the bending operation is 80,000 or more.
[0037] <fpc> The metal layer is subjected to wiring processing to form an FPC. There are no particular limitations on the wiring pattern, and wiring processing can be performed by a conventional method. The present invention also includes such an FPC.
[0038] <Coverlay> A coverlay may be laminated on the metal layer on which wiring has been processed. As the coverlay, a commercially available product in which an adhesive layer is laminated on a polyimide film can be used. The thickness of the coverlay is preferably within a range of 35 to 40 μm, and the tensile modulus of elasticity is preferably within a range of 2.0 to 3.5 GPa. Examples of such a coverlay include CEA0525 (product name) manufactured by Arisawa Manufacturing Co., Ltd.
[0039] <Loop stiffness> When a test specimen is cut from a portion of the metal layer of the metal-clad laminate of the present invention where no wiring is formed, the loop stiffness value of the test specimen is 1 N / m or more and 6 N / m or less, preferably 1 N / m or more and 3 N / m or less, more preferably 2.2 N / m or less, and even more preferably 2.1 N / m or less.
[0040] This loop stiffness value is the compression force (repulsion force) when a test piece with a width of 12.7 mm and a length of 165 mm is cut from the metal-clad laminate, and a loop stiffness tester manufactured by Toyo Seiki Co., Ltd. is used to join both ends of the test piece (metal-clad laminate) 100 to form a loop with a loop length of 60 mm as shown in FIG. 1, and the test piece 100 is sandwiched between the opposing indenter plates 21 and 22, and crushed under the conditions of a crushing speed of 3.3 mm / sec and a crushing distance of 15 mm. In the present invention, the loop stiffness value is measured by measuring the loop stiffness value in the MD direction (the longitudinal direction of the rolled metal-clad laminate). The smaller the loop stiffness value, the lower the stiffness, and the metal-clad laminate of the present invention has a lower stiffness than conventional metal-clad laminates.
[0041] Since the loop stiffness value is in the range of 1 N / m to 6 N / m, which is a lower value than that of the conventional metal-clad laminate, the FPC formed from the metal-clad laminate has excellent continuous bending properties and can withstand repeated 180° bending tests. Therefore, when a test piece 200 of an FPC having wiring 201 formed on a metal-clad laminate is bent as shown by the arrow in FIG. 3 to form a first non-bending portion 110, a second non-bending portion 120, and a bent portion 130 between the first non-bending portion 110 and the second non-bending portion 120, even if the cap G', which is the distance between the first non-bending portion 110 and the second non-bending portion, is narrow, the shape of the bent portion 130 is prevented from becoming an acute angle, and large stress is prevented from being applied locally. Furthermore, the metal-clad laminate is less likely to plastically deform, and it is possible to disperse stress in the bent portion 130 so that the bent shape is maintained in an arc shape. Therefore, even if 180° bending tests are performed continuously on an FPC formed from a metal-clad laminate, it is possible to prevent cracks or breaks due to metal fatigue from occurring in the wiring layer of the FPC, and to increase the number of bending cycles until the resistance value of the wiring layer of the FPC reaches a predetermined value.
[0042] On the other hand, if the loop stiffness value is too low, the metal-clad laminate will undergo plastic deformation, and stress will be concentrated in specific locations during repeated bending, resulting in bending fatigue that may cause cracks or breaks in the FPC wiring.
[0043] In addition, since the loop stiffness value of the metal-clad laminate is in the range of 1 N / m to 6 N / m, the metal-clad laminate exhibits low resilience, which suppresses peeling of the wiring layer during FPC manufacturing and after FPC processing, improving workability. In addition, since the FPC has low resilience, when the FPC is housed inside an electronic device, it is easy to bend the FPC to fit the shape and size of the internal space.
[0044] The loop stiffness value of the metal-clad laminate can be adjusted to the above-mentioned range by selecting the polyimide resin forming the polyimide insulating layer from the above-mentioned compounds, and setting the thickness of the polyimide resin layer, the thickness of the metal layer, and their total thickness as described above.
[0045] When an FPC formed from the metal-clad laminate of the present invention is used in a hinge portion of a foldable device that is repeatedly bent by 180 degrees, it is preferable to arrange the FPC so that the wiring 201 is on the inside when it is folded. This reduces stress compared to when the wiring is arranged on the outside, and improves bending resistance. EXAMPLES
[0046] The present invention will now be described in detail with reference to examples. As described below, copper-clad laminates and FPCs were produced in Examples 1 to 3 and Reference Examples 1 to 4, and the loop stiffness values were measured and bending resistance was evaluated by a continuous bending test. The results are shown in Table 1.
[0047] (1) Loop stiffness value A test piece (length 165 mm, width 12.7 mm) was cut from a metal-clad laminate without wiring processing, and the loop stiffness value in the MD direction (longitudinal direction) was measured using a loop stiffness tester (manufactured by Toyo Seiki Co., Ltd.) under conditions of a loop length of 60 mm, a crushing distance of 15 mm, and a crushing speed of 3.3 mm / sec.
[0048] (2) Continuous bending test The test was performed as follows using a bending resistance test apparatus similar to the bending resistance test apparatus described in JP 2019-113482 A.
[0049] First, the copper foil of the copper-clad laminate was etched to produce a test piece (test circuit board piece) 200 having a wiring width L of 100 μm, a space width S of 100 μm, a straight portion length A of 110 mm along the longitudinal direction of the copper-clad laminate, and a meandering wiring 201 with 16 straight rows, as shown in Fig. 2. Note that Fig. 2 shows only the wiring 201 in the test piece 200, and also shows a part of the straight portion of the 16 rows of wiring. The test piece 200 was set in a bending resistance test device, and a resistance measuring device (not shown) was connected to both ends 201a and 201b of the meandering wiring 201.
[0050] Next, monitoring of the resistance value was started with the resistance measuring device. In the bending resistance test device, as shown in FIG. 4A, the test piece 200 was placed on the stages 220 and 230 so that the wiring 201 faced upward.
[0051] As shown in FIG. 5A, stages 220 and 230 were rotated to bend test piece 200 so that wiring 201 faced each other on the inside, thereby forming first non-bent portion 110, second non-bent portion 120, and bent portion .
[0052] In addition, when the test piece 200 is bent, the lengths in the X-axis direction and the Y-axis direction in the deformation region of the bent portion 130 can be arbitrarily set by the distance S between the stages 220 and 230 before bending and the gap G between the stages 220 and 230 in the bent state. The lengths in the X-axis direction and the Y-axis direction in this test are shown in Table 1.
[0053] In the continuous bending test, the maximum number of bending cycles was 300,000. The point at which the resistance value increased by 10% or more from the value before the bending test was determined to be a failure. The number of bending cycles (number of flexions) up to that point was recorded as the measured value, and the average of the 10 measured values was recorded as the average number of flexions.
[0054] In the continuous bending test, as shown in FIG. 4B, stages 220, 230 having recesses 220a, 230b that also serve as shape control jigs for the bent portion of the test specimen are used as stages for placing the test specimen, and the test specimen 200 may be bent by rotating the stages 220, 230 so that the recesses 220a, 230a of the stages 220, 230 face each other as shown in FIG. 5B.
[0055] (3) Coefficient of thermal expansion (CTE) The polyimide films forming the copper-clad laminates of the Examples and Reference Examples were heated to 250°C using a Thermomechanical Analyzer manufactured by Seiko Instruments, and then held at that temperature for 10 minutes. The polyimide films were then cooled at a rate of 5°C / min to determine the average thermal expansion coefficient (linear thermal expansion coefficient) from 240°C to 100°C.
[0056] (4) Preparation of FPCs in Examples and Reference Examples (4-1) Synthesis of polyamic acid solution (Synthesis Example 1) N,N-dimethylacetamide was placed in a reaction vessel equipped with a thermocouple and a stirrer and capable of introducing nitrogen. 2,2-bis[4-(4-aminophenoxy)phenyl]propane (BAPP) was then added to the reaction vessel and dissolved in the vessel while stirring. Next, pyromellitic dianhydride (PMDA) was added so that the total amount of monomers added was 12 wt%. Stirring was then continued for 3 hours to carry out a polymerization reaction, yielding a resin solution of polyamic acid a. The coefficient of thermal expansion (CTE) of a 25 μm-thick polyimide film formed from polyamic acid a was 55×10 -6 / K.
[0057] (Synthesis Example 2) N,N-dimethylacetamide was placed in a reaction vessel equipped with a thermocouple and a stirrer and capable of introducing nitrogen. 2,2'-dimethyl-4,4'-diaminobiphenyl (m-TB) was then added to the reaction vessel and dissolved in the vessel while stirring. Next, 3,3',4,4'-biphenyltetracarboxylic dianhydride (BPDA) and pyromellitic dianhydride (PMDA) were added so that the total amount of monomers added was 15 wt% and the molar ratio of each acid anhydride (BPDA:PMDA) was 20:80. Stirring was then continued for 3 hours to carry out the polymerization reaction, and a resin solution of polyamic acid b was obtained. The thermal expansion coefficient (CTE) of a 25 μm-thick polyimide film formed from polyamic acid b was 22×10 -6 / K.
[0058] (4-3) Example 1 On copper foil 1 (rolled copper foil, long, thickness: 12 μm), the resin solution of polyamic acid a prepared in Synthesis Example 1 was uniformly applied so that the thickness after curing was 1.6 μm, and then the solution was heated and dried at 130 ° C to remove the solvent. Next, the resin solution of polyamic acid b prepared in Synthesis Example 2 was uniformly applied to the coated surface so that the thickness after curing was 5.0 μm, and the solution was heated and dried at 120 ° C to remove the solvent. Furthermore, the resin solution of polyamic acid a was uniformly applied to the coated surface so that the thickness after curing was 1.6 μm, and the solution was heated and dried at 130 ° C to remove the solvent. This long laminate 1 was heat-treated stepwise from 130 ° C to 360 ° C to obtain a single-sided copper-clad laminate (polyimide layer thickness: about 8 μm).
[0059] The same copper foil 1 as described above was thermocompression bonded at 300 to 400° C. to the surface of the polyimide layer of the single-sided copper-clad laminate to obtain a double-sided copper-clad laminate.
[0060] The copper foil layer on the bonding surface of the double-sided copper-clad laminate was etched away to obtain a single-sided flexible copper-clad laminate 1 (polyimide layer thickness: 8 μm, loop stiffness value: 1.71 N / m). The copper foil layer of the single-sided flexible copper-clad laminate 1 was processed into a wiring circuit to form copper wiring, and flexible circuit board 1 was obtained. When a continuous bending test was performed on flexible circuit board 1, the average number of bending times at which it was determined to have failed was 269,814, and the failure rate (hereinafter referred to as failure rate) when a continuous bending test of 300,000 bending times was performed simultaneously on multiple test pieces was 6 / 10.
[0061] (4-4) Example 2 On copper foil 1 (rolled copper foil, long, thickness: 12 μm), the resin solution of polyamic acid a prepared in Synthesis Example 1 was uniformly applied so that the thickness after curing was 2.3 μm, and then the solution was heated and dried at 130 ° C to remove the solvent. Next, the resin solution of polyamic acid b prepared in Synthesis Example 2 was uniformly applied to the coated surface so that the thickness after curing was 7.5 μm, and the solution was heated and dried at 120 ° C to remove the solvent. Furthermore, the resin solution of polyamic acid a was uniformly applied to the coated surface so that the thickness after curing was 2.3 μm, and the solution was heated and dried at 130 ° C to remove the solvent. This long laminate 1 was heat-treated stepwise from 130 ° C to 360 ° C to obtain a single-sided copper-clad laminate (polyimide layer thickness: about 12 μm).
[0062] Copper foil 1 was thermocompression bonded to the surface of the polyimide layer of the single-sided copper-clad laminate at 300 to 400° C. to obtain a double-sided copper-clad laminate.
[0063] The copper foil layer on the bonding surface of the double-sided copper-clad laminate was removed by etching to obtain a single-sided flexible copper-clad laminate 2 (polyimide layer thickness: 12 μm, loop stiffness value: 2.12 N / m). The copper foil layer of the single-sided flexible copper-clad laminate 2 was processed into a wiring circuit to form copper wiring, and flexible circuit board 2 was obtained. When flexible circuit board 2 was evaluated, the average number of flexing times was 121,669 (failure rate: 10 / 10).
[0064] (4-5) Example 3 A single-sided copper-clad laminate 3 (polyimide layer thickness: 12 μm), a double-sided copper-clad laminate 3, a single-sided flexible copper-clad laminate 3 (polyimide layer thickness: 12 μm, loop stiffness value: 2.37 N / m), and a flexible circuit board 3 were obtained in the same manner as in Example 2, except that copper foil 2 (electrolytic copper foil, long strip, thickness: 12 μm) was used instead of copper foil 1 in Example 2. When flexible circuit board 3 was evaluated, the average number of flexing times was 86,311 times (failure rate: 10 / 10).
[0065] (4-6) Reference example 1 The copper foil layer on one side of a commercially available double-sided flexible copper-clad laminate 4 (rolled copper foil, long strip, copper foil thickness: 12 μm, polyimide layer thickness: 25 μm) was removed by etching to obtain a single-sided flexible copper-clad laminate 4 (polyimide layer thickness: 25 μm, loop stiffness value: 6.38 N / m), and the copper foil layer was processed into a wiring circuit to form copper wiring, thereby obtaining a flexible circuit board 4. When the flexible circuit board 4 was evaluated, the average number of flexing cycles was 14,547 (failure rate: 10 / 10).
[0066] (4-7) Reference example 2 The copper foil layer on one side of a commercially available double-sided flexible copper-clad laminate 5 (electrolytic copper foil, long strip, copper foil thickness: 12 μm, polyimide layer thickness: 25 μm) was removed by etching to obtain a single-sided flexible copper-clad laminate 5 (polyimide layer thickness: 25 μm, loop stiffness value: 8.31 N / m), and the copper foil layer was processed into a wiring circuit to form copper wiring, thereby obtaining a flexible circuit board 5. When the flexible circuit board 5 was evaluated, the average number of flexing times was 16,015 (failure rate: 10 / 10).
[0067] (4-8) Reference example 3 A coverlay A (manufactured by Arisawa Manufacturing Co., Ltd., product name: CEA0525, thickness: 37.5 μm) was attached to the wiring side of the flexible circuit board 4 of Reference Example 1 to obtain a flexible circuit board 6. When the flexible circuit board 6 was evaluated, the average number of bending times was 151,400 times (failure rate: 3 / 5).
[0068] (4-9) Reference example 4 A coverlay A (thickness: 37.5 μm) was attached to the wiring side of flexible circuit board 5 of Reference Example 2 to obtain flexible circuit board 7. When flexible circuit board 7 was evaluated, the average number of flexions was 166,300 (failure rate: 3 / 5).
[0069] (5) Summary The above results are summarized in Table 1 and Figure 6. In Table 1, the LS value means the loop stiffness value, and CL means the coverlay.
[0070] [Table 1]
[0071] The results in Table 1 show that the flexible copper-clad laminates of Examples 1 to 3, which have loop stiffness values in the range of 1 N / m or more and 6 N / m or less, have a significantly improved average number of flexions until failure in a continuous bending test compared to Reference Examples 1 and 2. In addition, the average number of flexions in Reference Examples 3 and 4, in which a coverlay was provided, exceeded those in Examples 2 and 3. However, according to the present invention, it is clear that an average number of flexions equal to or greater than that in which a coverlay is provided can be achieved even without providing a coverlay. [Explanation of symbols]
[0072] 21, 22 Indenter plate 100 test pieces, metal clad laminate 110 First non-bending portion 120 Second non-bending portion 130 Bend 200 test pieces, FPC 201 Serpentine wiring, wiring 220, 230 Stages 220a, 230b Recess G, G' Gap L Width of wiring S Space width< / fpc>
Claims
1. A metal-clad laminate comprising a metal layer laminated on one surface of a polyimide insulating layer including a single or multiple polyimide layers, The total thickness of the polyimide insulating layer is within a range of 6 to 10 μm, a metal-clad laminate for a flexible circuit board for electronic components, in which an operation of bending the second non-bent portion 180° with respect to the first non-bent portion is repeated so as to have a shape including a first non-bent portion and a second non-bent portion whose shape has not changed compared to a flat state, and a bent portion that is located between the first non-bent portion and the second non-bent portion and that has been curved and deformed; The loop stiffness value (width 12.7 mm, loop length 60 mm, crushing distance 15 mm) of the test piece of the metal-clad laminate is 1 N / m or more and 2.1 N / m or less, A metal-clad laminate comprising a polyimide constituting a main layer of the polyimide insulating layer, the polyimide containing tetracarboxylic acid residues and diamine residues, the tetracarboxylic acid residues containing at least one of tetracarboxylic acid residues derived from pyromellitic dianhydride or tetracarboxylic acid residues derived from 3,3',4,4'-biphenyltetracarboxylic dianhydride in a total amount of 50 or more mole parts per 100 mole parts of all tetracarboxylic acid residues, and a diamine residue derived from a diamine compound represented by the following general formula (1) in an amount of 50 or more mole parts per 100 mole parts of all diamine residues: 【Chemistry 1】 [In formula (1), the linking group Z represents a single bond or -COO-, Y represents a monovalent hydrocarbon having 1 to 3 carbon atoms, an alkoxy group having 1 to 3 carbon atoms, or a perfluoroalkyl group having 1 to 3 carbon atoms, or an alkenyl group, which may be substituted with a halogen or a phenyl group, n represents 1 or 2, and p and q independently represent integers of 0 to 4.]
2. 2. The metal-clad laminate according to claim 1, wherein the ratio of the thickness of said polyimide insulating layer to the thickness of said metal layer is 0.3 to 1.
0.
3. When a meandering wiring having parallel straight portions with an L / S of 100 μm / 100 μm and a length of 110 mm is formed in the metal layer, and the metal-clad laminate is bent so that the longitudinal direction of the wiring is folded in half, and an operation of inverting and bending the second non-bent portion by 180° with respect to the first non-bent portion is repeated so as to form a first non-bent portion, a second non-bent portion, and a bent portion between the first non-bent portion and the second non-bent portion, An axial direction parallel to the thickness direction of the first non-bent portion and the second non-bent portion is defined as a Y-axis direction, and an X-axis direction perpendicular to the Y-axis direction and extending in the longitudinal direction of the wiring of the non-bent portion is defined as an X-axis direction.
3. The metal-clad laminate according to claim 1 or 2, wherein when the maximum length of the bent portion in the X-axis direction is 1.0 mm or more and 10.0 mm or less and the maximum length of the bent portion in the Y-axis direction is 1.0 mm or more and 6.0 mm or less in two-dimensional coordinate axes in the X-axis direction and the Y-axis direction, the number of bendings at the point where the resistance has increased by 10% compared to before the bending operation started is 80,000 or more.
4. The metal-clad laminate according to any one of claims 1 to 3, wherein the total thickness of the polyimide insulating layer and the metal layer is 15 µm or more and 36 µm or less.
5. A double-sided metal-clad laminate comprising a metal layer on the other side of the polyimide insulating layer in the metal-clad laminate according to any one of claims 1 to 4.
6. A flexible circuit board having a metal layer of the metal-clad laminate according to any one of claims 1 to 4, which is wired.
7. 7. The flexible circuit board according to claim 6, for a circuit in which a folding operation is repeatedly performed in a state where the metal layer is folded inward and then in a state where the folded state is straightened.
Citation Information
Patent Citations
Copper-clad laminated sheet
JP2007313854A
Flexible copper-clad laminate plate
JP2014080021A
Flexible circuit board and electronic apparatus
JP2016146419A
Polyimide film
JP2018168358A
Metal-clad laminate and circuit board
JP2019104233A